Management of Dystocia Due to Fetal Anomaly in Sheep - P.Venkata Sai kumar; P.Utkarsha; Satish martha; M.Rajashri; E.Sunil Anand Kumar (The Indian Veterinary Journal, 2023)
A 5yr old non-descript ewe presented at TVCC, Mamnoor with history of straining since 24hrs. Per-vaginal examination revealed an oversized dead fetus with downward deviation of head and neck. The dystocia was successfully relieved by application of william’s long obstetrical hook and by performing partial fetotomy.